Correction: Identification of a 3rd Na+ Binding Site of the Glycine Transporter, GlyT2. - Nandhitha Subramanian; Amanda J Scopelliti; Jane E Carland; Renae M Ryan; Megan L O'Mara; Robert J Vandenberg (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0157583.].